Therapeutic effects of anthocyanin-rich Hibiscus sabdariffa L. extract on body mass index, lipid profile and fatty liver in obese-hypercholesterolaemic rat model - Noordin, Liza; Wan Mohamad Noor, Wan Nurul Izzati; Safuan, Sabreena; Wan Ahmad, Wan Amir Nizam (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Hibiscus sabdariffa L. or Roselle, is one of the most common flower plants cultivated worldwide. Traditionally, it is claimed to reduce weight and cholesterol level. The aim of this study was to evaluate the effects of anthocyanin-rich Roselle aqueous extract on the physical, biochemical and histological changes in obese-hypercholesterolaemic rat model. Methods: Thirty Sprague-Dawley male rats were divided into five groups (n=6 per group). Group 1 is normal control (NC) rat that was fed with normal diet. The remaining rats (Group 2-5) were fed with commercial high-fat diet (HFD) for 6 weeks to induce obese-hypercholesterolaemic (OH) rat. After induction, the OH rats were divided into 4 groups: OH-Untreated group, OH-ARTE; OH treated with 300 mg/kg Roselle aqueous (anthocyanin-rich) and 1% trifluoroacetic acid extract (ARTE), OH-Orlistat; OH treated with 37 mg/kg orlistat and OH-Atorvastatin; OH treated with 10 mg/kg atorvastatin. After the 3 weeks intervention period, all rats were sacrificed. Body mass index, lipid profile and liver enzymes were evaluated. The liver section was subjected to hematoxylin and eosin staining for histopathological evaluation. Results: This study showed that 3 weeks administration of ARTE significantly reduced BMI, improved levels of lipid profile and liver enzymes, and histopathological changes of liver when compared to OH-untreated rats. The results were also comparable to the standard drugs. Conclusions: This study suggested that Roselle extract constitutes an effective and safe alternate treatment for obesity and hyperlipidaemia.